1991
DOI: 10.3801/iafss.fss.3-237
|View full text |Cite
|
Sign up to set email alerts
|

A Study Of The Fire Performance Of Electrical Cables

Abstract: Experimental results are presented of the piloted ignition delay time and the upward flame-spread rate over the surfaces of insulated electrical cables under an externally applied radiant flux. The objective of the experiments was to assess and rank the fire performance of seven types of complex cables commonly used in electrical installations. The experiments were carried out with 46 em long single cables that were suspended vertically and exposed to irradiance levels ranging from 0.5 -2.5 W/cm 2 • Some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…The flame propagation test of electrical wires at inclination was studied in NASA's standard test [6]. Fernandez-Pello et al [7] experimentally studied the fire performance of several electrical wires and predicted their ignition delay time theoretically. Leung et al [8] simulated the effect of the central core on thermal pyrolysis of the insulation layer without flame during the heating process.…”
Section: Introductionmentioning
confidence: 99%
“…The flame propagation test of electrical wires at inclination was studied in NASA's standard test [6]. Fernandez-Pello et al [7] experimentally studied the fire performance of several electrical wires and predicted their ignition delay time theoretically. Leung et al [8] simulated the effect of the central core on thermal pyrolysis of the insulation layer without flame during the heating process.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports21, 22 showed that TGA is a feasible tool for predicting, fairly accurately, the time to ignition for pure polymers. Briefly, in both these studies, the TGA was preheated to a given temperature and the sample was inserted and heated isothermally.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, in both these studies, the TGA was preheated to a given temperature and the sample was inserted and heated isothermally. The second inflection of the temperature–time curve21 or the initiation of the weight loss temperature22 (defined by the authors as the temperature at which the mass loss curve separates from the zero weight loss position and assumed to be the same as the ignition temperature) was recorded. Further, the value of this characteristic temperature was plugged into the flame‐spread equations and the time to ignition was calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire spread rate prediction is critical for fire risk assessment and fire safety design, and numerous studies have been conducted on the spread of fire in buildings over the last few decades [1]. In particular, the electrical cables used for various elements in housing and industrial environments pose a constant risk of electrical fires, which account for the largest portion of fires, and the cables themselves can act as ignition sources, inducing large-scale fire or secondary combustibility [2]. As an applied example of electric-cable-induced fire, research on ignition and fire spread due to cable malfunction has been conducted under special conditions such as the microgravity environment of a space station [3,4].…”
Section: Introductionmentioning
confidence: 99%